Environmental Problems of Solid Waste at the Present Stage - Madraim Khasanovich Sarikulov (Scientific Trends, 2025)
This article is devoted to the problem of solid waste as one of the most undesirable negative factors at the present stage. The environmental problems of solid waste at the present stage are considered in the context of water and food poisoning, environmental pollution, which poses a great threat to society, and will also negatively affect the health of the population. A comparative analysis of the causes of environmental problems of solid waste in the modern world is given.
Keywords: Solid waste, environmental risks, environmental initiatives, toxic substances and compounds, organic pathogens, waste recycling, waste minimization.